Assisting the least among us: Social work's historical response to unaccompanied immigrant and refugee youth. (September 2018) - Jani, Jayshree S.; Reisch, Michael
Abstract: Unaccompanied immigrant and refugee youth enter the U.S. daily to escape violence, political oppression, extreme poverty, and chronic instability in their native countries, or as victims of human trafficking. In FY 2016, nearly 60, 000 UAC arrived from Central America and Mexico alone (ORR, 2017) and officials estimate that UAC will continue to enter the U.S. at a rapid pace in the years ahead. Yet, because these youth do not have the same legal status, the government treats them differently upon their arrival (Cebulko, 2013). Recent executive orders by the Trump Administration have exacerbated this problem and underscore the importance of providing comprehensive supportive services to this population. However, there is a dearth of scholarship on this issue, and scant evidence that current programs are effective in protecting vulnerable children (Bhabha, 2004). This challenge is not new. In different eras social workers have addressed the needs of this population through a combination of private and state-sponsored interventions. Several factors influenced these varied responses: (1) the changing demographic and national characteristics of UAC and the range of needs they exhibited; (2) prevailing attitudes toward immigrants and refugees, often influenced by the status of the U.S. economy; and (3) the distribution of responsibilities between the public and private sectors for the development, implementation, and funding of programs that addressed the needs of UAC. Based on primary and secondary source materials, this article traces the evolution of social work's response to these needs during the past two centuries. It identifies some common and conflicting themes in the profession's assessment of the issues faced by UAC, and the purposes and outcomes of the interventions developed. It concludes by examining how the treatment of this population reflected the goals of assimilation, exclusion, or structural change, and how these goals continue to influence contemporary policy and practice. Highlights: Historically, social workers have addressed the needs of UAC in varying ways depending on demographics of youth, and the sociopolitical climate. An unresolved issue is whether services to UAC should promote assimilation into mainstream society or maintain their exclusion. Private organizations have been the primary responders to the needs of UAC while government programs are largely underfunded and lack planning. Further research is necessary regarding the effectiveness and outcomes of programs serving unaccompanied youth.